2021
DOI: 10.3390/molecules26247589
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Carnosic Acid on Lipopolysaccharide-Induced Acute Kidney Injury in Mice

Abstract: Septic acute kidney injury (AKI) is an important medical problem worldwide, but current treatments are limited. During sepsis, lipopolysaccharide (LPS) activates various signaling pathways involved in multiorgan failure. Carnosic acid is a natural phenolic diterpene and has multiple bioactivities, such as anti-tumor, anti-inflammatory, and anti-oxidative effects. However, the effect of carnosic acid on septic AKI has not been explored. Therefore, this study aimed to determine whether carnosic acid has a therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…The tissue blocks were sectioned and stained with hematoxylin and eosin (H&E) or periodic acid-Schiff (PAS). Tubular injury score was assessed in 5 randomly selected fields per sample, as previously described [ 14 , 15 ]. For IHC, primary antibodies against neutrophil gelatinase-associated lipocalin (NGAL; Santa Cruz Biotechnology, Santa Cruz, CA, USA), kidney injury molecule-1 (KIM-1; Santa Cruz Biotechnology), 4-hydroxy-2-nonenal (4-HNE; Invitrogen, Carlsbad, CA, USA), F4/80 (Santa Cruz Biotechnology), and CD4 (Novus Biologicals, Littleton, CO, USA) antibodies were used.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue blocks were sectioned and stained with hematoxylin and eosin (H&E) or periodic acid-Schiff (PAS). Tubular injury score was assessed in 5 randomly selected fields per sample, as previously described [ 14 , 15 ]. For IHC, primary antibodies against neutrophil gelatinase-associated lipocalin (NGAL; Santa Cruz Biotechnology, Santa Cruz, CA, USA), kidney injury molecule-1 (KIM-1; Santa Cruz Biotechnology), 4-hydroxy-2-nonenal (4-HNE; Invitrogen, Carlsbad, CA, USA), F4/80 (Santa Cruz Biotechnology), and CD4 (Novus Biologicals, Littleton, CO, USA) antibodies were used.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence (IF) staining for lotus tetragonolobus lectin (LTL), a marker of the tubule brush border [ 26 ], revealed that LPS injection markedly induced brush border loss in the tubules, and hispidulin administration significantly reversed these changes (LPS, 7.8 ± 1.8 % vs. LPS + His, 26.3 ± 4.0 %, p < 0.001; Figure 3 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Serum creatinine and BUN levels were measured to assess kidney function. These indicators are widely used in animal experiments to evaluate kidney function [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. We found that hispidulin significantly attenuated the LPS-induced renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of LPS can lead to rapid and transitory increases in pro-inflammatory cytokines such as TNF-α and IL-6 in mammals [ 52 ]. As a result, LPS injection stimulates acute inflammatory responses in various organs, including the kidney, brain, lung, and liver [ 53 , 54 ]. In our experiment, LPS injection triggered systemic dyslipidemia by increasing TG, TC, and LDL-C levels and decreasing HDL-C levels in obese mice ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%